SCIENTIFIC EVOLUTION AND TEACHING OF THE LAW OF CIVIL PROCEDURE IN THE LAST 6 DECADES IN COSTA RICA - López González, Jorge (2023)
This work contains reference to the civil procedural doctrine that has been published by the Revista de Ciencias Jurídicas during the last sixty years. These publications explain the situation of civil procedural legislation, its defects and practical problems. In some the exposition is merely descriptive and in others solutions are offered. In the second part, reference is made to the importance of the study of Procedural Law and the perspectives on teaching from the point of view of teaching resources and learning techniques.